THE EFFECT OF GIVING PINEAPPLE PEEL EXTRACT (Ananas comosus L. Merr) IN DRINKING WATER ON WEIGHT AND COMMERCIAL CARCASS PIECES OF JOPER CHICKENS - ., Dinda; Siti, N. W.; Oka, A.A. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aimed to determine the effect of giving pineapple peel extract in drinking water on commercial carcass pieces of joper chickens. This research was carried out for 6 weeks at Teaching Farm Faculty of Animal Husbandry, Udayana University, Bali. The experimental design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications, so there were 20 experimental units. Each experimental unit contained 3 heads joper chickens aged 2 weeks and a total of 60 joper chickens were used. The treatments given were joper chickens given drinking water without pineapple peel extract (P0), joper chickens given drinking water with 6% pineapple peel extract (P1), joper chickens given drinking water with 8% pineapple peel extract (P2), joper chickens given drinking water with 10% pineapple peel extract (P3). The variables observed were slaughter weight, carcass weight, carcass percentage and percentage of commercial carcass pieces (breast, thigh muscle, drumstick, back, and wing). The results showed that joper chickens were given treatment P1, P2, P3 had no significant effect and P0 on slaughter weight, carcass weight, carcass percentage and percentage of commercial carcass in pieces. Based on the results of the study it can be concluded that giving pineapple peel extract in drinking water at levels of 6%, 8% and 10% has not been able to increase slaughter weight, carcass weight, carcass percentage and percentage of commercial carcass pieces.